Reducing international graduate students' language anxiety through oral pronunciation corrections. (February 2016) - Lee, Eun Jeong (Esther)
Abstract: This mixed methods study examines the relationships between teachers' oral corrective feedback (CF) and changes in international graduate students' language anxiety levels. The participants were sixty advanced-level adult ESL students, all of whom were training to be teaching assistants (TAs) at a large Midwestern US university. The data were collected through classroom observations, survey questionnaires (pre- and post-surveys), and in-depth follow-up interviews with 40 of the 60 students. The study revealed that most of the teachers' oral CF had positive impacts on the students' affective variables, specifically lowering their anxiety about speaking English. However, certain clarification requests increased the students' anxiety instead. These results highlight the potential affective risks of CF, and the study suggests how ESL instructors can use CF to encourage or even create positive emotional states in their ESL students.